2008
DOI: 10.1371/journal.pbio.0060037
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deficiency of Glycogen Synthase Kinase-3β Corrects Diabetes in Mouse Models of Insulin Resistance

Abstract: Despite treatment with agents that enhance β-cell function and insulin action, reduction in β-cell mass is relentless in patients with insulin resistance and type 2 diabetes mellitus. Insulin resistance is characterized by impaired signaling through the insulin/insulin receptor/insulin receptor substrate/PI-3K/Akt pathway, leading to elevation of negatively regulated substrates such as glycogen synthase kinase-3β (Gsk-3β). When elevated, this enzyme has antiproliferative and proapoptotic properties. In these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 53 publications
(65 reference statements)
6
102
0
Order By: Relevance
“…Indeed, our data dovetail with a previous work showing that the overexpression of a dominant-negative Pkb (also known as Akt) in beta cells leads to impaired insulin secretion [45]. Recent facts have been reported showing that GSK-3β activation is linked to beta cell failure in diabetic mouse models, and is involved in negative regulation of beta cell proliferation and mass [46,47]. Moreover, GSK-3β activity is enhanced in insulin-resistant states, and in skeletal muscle from type 2 diabetic patients [48].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, our data dovetail with a previous work showing that the overexpression of a dominant-negative Pkb (also known as Akt) in beta cells leads to impaired insulin secretion [45]. Recent facts have been reported showing that GSK-3β activation is linked to beta cell failure in diabetic mouse models, and is involved in negative regulation of beta cell proliferation and mass [46,47]. Moreover, GSK-3β activity is enhanced in insulin-resistant states, and in skeletal muscle from type 2 diabetic patients [48].…”
Section: Discussionsupporting
confidence: 89%
“…Also, several studies using animal models of diabetes showed the importance of downregulation or loss of p27 in b-cells for accelerating replication of b-cells and thereby expansion of b-cell mass for correcting diabetes. [36][37][38] We have found robust interaction of p27 with GSK-3 in human islets and rodent b-cells (Fig. 2).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 78%
“…Studies using in-vitro and in-vivo models have demonstrated that GSK-3 inactivation/deficiency results in p27 instability/degradation. 31,37 Also, increased proliferation of both primary and transformed rodent b-cells following GSK-3 inactivation by small molecule inhibitors including BIO or 1-AKP have been reported. 39 A study demonstrated increased proliferation of highly differentiated primary rodent cardiomyocytes after BIO-mediated GSK-3 inhibition.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Further complicating understanding, the strategy used in these models (mutation of the inhibitory serine 21 phosphorylation site of GSK-3α and serine 9 phosphorylation site of GSK-3β to alanine residues) blocks only 1 mechanism by which GSK-3α can be inhibited (i.e., PI3-kinase-mediated activation of Akt) and does not affect Wntmediated or p38-MAPK-mediated inhibition (15)(16)(17). Finally, to date, no studies have examined possible metabolic effects of GSK3s and how they might affect cardiac function, even though this is a critical factor in GSK-3-regulated disease processes, including glucose intolerance and diabetes (18,19).…”
Section: Introductionmentioning
confidence: 99%